Studi Penetrasi Aplikasi Media Sosial Tik-Tok Sebagai Media Pemasaran Digital: Studi Kasus Kota Batam - Tony Wibowo; Yudi Yudi (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Marketing is an activity that is currently carried out by many people, ranging from marketing in the field of fashion, food, even developers also have their own marketing fields. With the development of the times, the way a person does marketing also develops. Digitalization has been in various places and of course marketing has also begun to develop into digital marketing where marketing is done using various media that use the internet, one of which is social media such as tiktok. By examining the research that has been done previously about the influence of tiktok on the world of digital marketing, we will conclude how big the impact of tuktok on the world of digital marketing today. From the results studied, it was concluded that tiktok as a digital marketing media or digital marketing has s significant impact because with social media we can sell our services to places we can’t even reach and of course we can increase sales with people we’ve never met